COPPER MOBILITY IN THE EASTERN CREEK VOLCANICS, MOUNT ISA, AUSTRALIA: EVIDENCE FROM LASER ABLATION ICP-MS OF IRON-TITANIUM OXIDES - Gregory M.J. (My University, 2006)
The Palaeoproterozoic Eastern Creek Volcanics are a series of copper-rich tholeiitic basalts which occur adjacent to the giant sediment-hosted Mount Isa copper deposit in Queensland, Australia. The volcanic rocks are often cited as the source of metals for the deposit. New laser ablation ICP-MS analyses of iron–titanium oxides from the basalts provide evidence for the local mobilisation of copper during regional greenschist facies metamorphism. This interpretation is based on the observation that copper-bearing magmatic titanomagnetite was destabilised during greenschist facies metamorphism, and the new magnetite which crystallised was copper poor. Petrological observations, regional geochemical signatures and geochemical modelling suggest that the mobilised copper was concentrated in syn-metamorphic epidote-rich alteration zones, creating a pre-concentration of copper before the main mineralisation event at Mount Isa. Geochemical modelling demonstrates this process is enhanced by the addition of CO2 from adjacent carbonate-rich sediments during metamorphic devolatilisation. Regional geochemical data illustrate elevated copper concentrations in epidote-rich zones (high CaO), but where these zones are overprinted by potassic alteration (high K2O), copper is depleted. A two-stage model is proposed whereby after metamorphic copper enrichment in epidote–titanite alteration zones, an oxidised potassium-rich fluid leached copper from the epidote-altered metabasalts and deposited it in the overlying sedimentary rocks to form the Mount Isa copper deposit. This ore-forming fluid is expressed regionally as potassium feldspar-rich veins and locally as biotite-rich alteration, which formed around major fluid conduits between the metabasalt metal source rocks and the overlying deposit host sequence. This model is consistent with the remobilisation of copper from mafic source rocks, as has been found at other world-class copper deposits.
Keywords: EASTERN CREEK VOLCANICS; MOUNT ISA; AUSTRALIA; COPPER; IRON-TITANIUM OXIDE GEOCHEMISTRY; LASER ABLATION ICP-MS; Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская